2015
DOI: 10.1007/s40520-015-0348-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional gain following knee replacement in patients aged 75 and older: a prospective follow-up study

Abstract: Avainsanat: tekonivelleikkaus, nivelrikko, päivittäistoiminnot, toimintakyky Tausta ja tavoitteet: Nivelrikko on maailman yleisin nivelsairaus. Esiintyvyys kasvaa iän myötä siten, että yli 80-vuotiaista ainakin kolmannes kärsii taudista. Tekonivelleikkaus on vakiintunut nivelrikon hoidoksi, ja leikkausmäärät ovat kasvussa. Leikkaus parantaa toimintakykyä, vähentää kipua ja on kustannusvaikuttava. On kuitenkin epäselvää, ketkä hyötyvät leikkauksesta eniten. Aiemmat tulokset sairauksien ja lihavuuden vaikutukses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…In Vekama et al’s study, of 167 patients, only 5 had preexisting dementia. 25 The study found that the effect of dementia on ADL performance 1 year postoperatively was not significant. However, ADL survey results were self-reported.…”
Section: Resultsmentioning
confidence: 92%
“…In Vekama et al’s study, of 167 patients, only 5 had preexisting dementia. 25 The study found that the effect of dementia on ADL performance 1 year postoperatively was not significant. However, ADL survey results were self-reported.…”
Section: Resultsmentioning
confidence: 92%
“…Twenty studies relied solely on the KL grading system [3, 14, 18, 22, 25, 27–30, 32, 34–39, 41, 42] or a modification of it [5, 15]. Five studies relied on a combination of KL grades with either joint space narrowing or Ahlbaeck score [8, 13, 21, 33, 40]. Two studies relied only on joint space narrowing [19, 23] and two studies relied only on the Ahlbaeck classification or a modification of it [4, 9].…”
Section: Resultsmentioning
confidence: 99%
“…The Visual Analog Scale (VAS) was used in six studies [21, 25, 29, 30, 33, 42]. 23 studies specifically reported on function [3–5, 9, 13, 14, 18, 19, 22, 25, 27, 28, 30, 33, 36–42]. 22 studies reported on pain [4, 5, 9, 13, 14, 19, 25, 27, 28, 30, 33, 36–39, 41, 42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that patients with a poorer functional score at baseline often derive the most gain in physical function [17]. Furthermore, patients with severe osteoarthritis following TKA have been observed to exhibit greater functional gain even if their final ability was low [27]. Here, we used the M-FIM score for the assessment of rehabilitation effectiveness, which is designed to overcome the ceiling effect of disability measures.…”
Section: Discussionmentioning
confidence: 99%